A rapid whole blood solubility test to differentiate the sickle-cell trait from sickle-cell anaemia. Issue 9 (December 1970) - Huntsman, R. G.; Barclay, G. P. T.; Canning, D. M.; Yawson, G. I.
Abstract : A simple and rapid screening test which differentiates sickle-cell trait and sickle-cell anaemia is described. The test utilizes 0·1 ml of whole blood and is based on the low solubility of reduced sickle haemoglobin. Results intermediate between the sickle-cell trait and sickle-cell anaemia are obtained in unusual cases of sickle-cell anaemia with high foetal haemoglobin. The need to supplement the results with haematological and electrophoretic techniques is discusses.